PERSPEKTIF DAN MINAT MAHASISWA UNTUK BERINVESTASI DI PASAR SAHAM MODAL SYARIAH SEBAGAI ALTERNATIF INVESTOR PEMULA - Rahmawati, Novia; Ria Sansitika, Desy; Azmi, Zul; Hamzah, Zulfadli (Research in Accounting Journal (RAJ), 2022)
Investing is an activity that is recommended from an Islamic point of view. This is because the Prophet Muhammad SAW has been involved in investment activities from a young age until he became apostolic. One of Indonesia's efforts to encourage economic growth is to expand the investment sector through the use of capital market products. This research is a descriptive and qualitative analysis. Islamic capital market activities are needed to further optimize the existence of Islamic law because the value of sharia in investing in sharia has not been fully investigated. Given the Islamic capital market position and a very strategic role in national economic activities